Self-efficacy of catering students of Faculty Technical and Vocational Education, University Tun Hussein Onn Malaysia in the Field of Career to be pursued - Ahmad Idris, N. S.; Abdullah, N. H. L.; M. Mohamed, M. Mohamed; Paimin, A. N. (2021)
The increasing rate of unemployed graduates in Malaysia has received alarming attention in recents years. One of the factors that contribute to the unemployment problem is the lack of self-efficacy among graduates in making career choices. Therefore, this study was conducted to identify the self-efficacy of catering students to make decision on career field options to be pursued either as a teacher, hospitality employee or entrepreneur. The design of this study is a quantitative descriptive study through survey and questionnaire is used as research instruments. A total of 66 catering students of year 3 and 4 from Faculty of Technical and Vocational Education (FPTV) were selected as the study sample. The data obtained were analyzed using Statistical Package for Social Science (SPSS) version 22.00 software involving mean, standard deviation, and ANOVA. The results showed that the mean scores of self-efficacy of catering students were high to become teachers (M= 4.11, SD=0.617) and followed by hospitality employee (M= 3.87, SD= 0.574) and entrepreneurs (M= 3.93, SD=0.514). However, there was no significant difference between the three career fields with a value of p = 0.052. In conclusion, catering students have high self-efficacy in venturing into the field of career when graduating from university. Graduates need to see the importance of enhancing self-efficacy because it opens paths for career opportunities and advancement.